MORPHOLOGICAL EVALUATION OF FOLLICLES AND OOCYTES IN ADULT GADDI GOAT - SURI, SHALINI; KALITA, A (The Indian Journal of Animal Reproduction, 2023)
Ovaries from 10 healthy adult female Gaddi goats were collected and their biometrical parametersand visible follicles were recorded. The visible surface follicles were classified into small, medium andlarge categories. The number of follicles was more in left ovary when compared to right ovary. However,the recovery of oocytes from follicles was more in right ovary rather than the left. The A and B types ofoocytes were maximum recovered from all three categories of follicles. The diameter of oocytes withzona pellucida was recorded maximum in A type whereas thickness of zona pellucida was maximum inC and N types of oocytes.
Keywords: Follicles; Oocytes; Gaddi goat